Market reaction to non-GAAP earnings around SEC regulation. Issue 3 (December 2017) - Bond, David; Czernkowski, Robert; Lee, Yong-Suk; Loyeung, Anna
Abstract: This study examines the impact of Regulation G in 2003 and the issuance of Compliance and Disclosure Interpretations (C&DIs) in 2010 – on the reporting of non-GAAP earnings. The study finds that (i) both Regulation G and C&DIs are associated with an increase in the quality of non-GAAP earnings exclusions (i.e. the exclusions are more transitory and have less predictive power for future operating earnings). (ii) Regulation G led to a decrease in the amount of total positive exclusions used to meet or beat analysts' forecasts, but C&DIs partially reversed this result. (iii) Regulation G increases, and C&DIs decrease, the earnings response coefficients (ERCs).